Inbred Mice Again at Stake: How the Cognitive Profile of the Wild-Type Mouse Background Discloses Pathogenic Effects of APP Mutations - Ammassari-Teule, Martine (Frontiers in Behavioral Neuroscience, 2022)
Increasing efforts have been made in the last decades to increase the face validity of Alzheimer’s disease (AD) mouse models. Main advancements have consisted in generating AD mutations closer to those identified in humans, enhancing genetic diversity of wild-type backgrounds, and choosing protocols much apt to reveal AD-like cognitive dysfunctions. Nevertheless, two aspects remain less considered like the cognitive specialization of inbred strains used as recipient background of mutations, and the heuristic importance of studying destabilization of memory circuits in pre-symptomatic mice facing cognitive challenges. This article underscores the relevance of these behavioral/experimental aspects by reviewing data which show that (i) inbred mice differ in their innate predisposition to rely on episodic vs procedural memory, which implicates differential sensitivity to mutations aimed at disrupting temporal lobe-dependent memory (ii) investigating training-driven neural alterations in asymptomatic mutants unveils early synaptic damage which considerably anticipate detection of AD first signs.